2014
DOI: 10.1017/s1473550414000329
|View full text |Cite
|
Sign up to set email alerts
|

Stellar statistics along the ecliptic and the impact on the K2 mission concept

Abstract: K2 is the mission concept for a repurposed Kepler mission that uses two reaction wheels to maintain the satellite attitude and provide ∼85 days of coverage for ten 105-deg 2 fields along the ecliptic in the first 2.5 years of operation. We examine stellar populations based on the improved Besançon model of the Galaxy, comment on the general properties for the entire ecliptic plane, and provide stellar occurrence rates in the first 6 tentative K2 campaigns grouped by spectral type and luminosity class. For each… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…These values are only approximate measures and are only as accurate as the polyfits themselves. Nevertheless, they do provide some measure of the signal-to-noise and also allow for an estimate of eccentricities (Prša et al 2015).…”
Section: Classification Of Light Curvesmentioning
confidence: 99%
See 1 more Smart Citation
“…These values are only approximate measures and are only as accurate as the polyfits themselves. Nevertheless, they do provide some measure of the signal-to-noise and also allow for an estimate of eccentricities (Prša et al 2015).…”
Section: Classification Of Light Curvesmentioning
confidence: 99%
“…Galaxy population observations and models, however, have long predicted this behavior: the stellar population at lower galactic latitudes (thin disk) contains notably younger stars that are on average larger (i.e. contain more giants in the magnitude-limited sample) than the older, sparser population of the thick disk and halo (Prša et al 2015). In consequence, the geometric probability of eclipses increases towards the galactic disk.…”
Section: Catalog Analysismentioning
confidence: 99%
“…5), as described in Prša et al (2011). This analytic function is then used to determine the morphology, a value between zero (detached) and one (overcontact), using locally linear embedding (Matijevič et al 2012).…”
Section: Eb Ephemerides and Morphologiesmentioning
confidence: 99%
“…The Kepler satellite (Batalha et al 2010) observed over 150,000 stars in its original mission, which acquired over 4 yr of high-precision photometry. This dataset was followed by a large effort to study the eclipsing binary (EB) population in the Kepler field, resulting in the detection and characterization of over 2500 EB stars (Prša et al 2011;Slawson et al 2011), the measurements of eclipse timing variations (Conroy et al 2014), and the discovery of several circumbinary planets (Doyle et al 2011;Welsh et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation